Опіка і виховання дітей-сиріт у діяльності асоціацій і приватних фондів Польщі в ХІХ ст. - Дзбинська, Христина (Studies in Comparative Education, 2013)
У статті висвітлено діяльність асоціацій (Краківської асоціації Опікунської Ради, Асоціації благодійних жінок сиротинця у Новому Сончі) та приватних фондів на польських землях у ХІХ ст., які виконували суттєву роль в організації опікунсько-виховної роботи з дітьми-сиротами. Головним їхнім завданням було забезпечення необхідних умов для проживання, початкового і професійного навчання сиріт, організації вільного часу. Як недолік відзначено відсутність єдиної системи навчання, оскільки кожен заклад працював за індивідуальним планом. В статье отражена деятельность ассоциаций (Краковская ассоциация Попечительского Совета, Ассоциация благотворительных женщин приюта в Новом Сонче) и частных фондов на польских землях в XIX в., которые выполняли существенную роль в организации попечительского-воспитательной работы с детьми-сиротами. Главной их задачей было обеспечение необходимых условий для проживания, начального и профессионального обучения сирот, организации свободного времени. Недостатком было отсутствие единой системы обучения, поскольку каждое заведение работало по индивидуальному плану. The article makes clear work of associations (Krakow association Tutorial Council, Association charitable women of the orphan-house in New Sonch) and private funds on the Polish land in 19th Century, which fulfilled an essential role in the organization of tutorial-upbringing work with the orphan-children. The aim of creating of association was providing for orphan-children guardianship and a good upbringing, vocational education and protection against poverty. To its structure belonged experts of different fields, especially: judges, members of municipal communities for orphan-children, representatives of district councils, pedagogues who worked at orphans’ or waifs and strays upbringing, representatives of educational establishments and associations. The main their task was providing with necessary living conditions, primary education and professional training of the orphans, arrangement of spare time. The youngest children studied after the curriculum of popular school. The elder pupils studied at the secondary school. School plan responded to that time demands of the region. It was even enlarged in relation with needs of pupils and included in addition religion, singing, music, agriculture and vegetable growing, painting and elements of theoretical vocational education. In the orphanage much attention was paid to the physical development of disciples and were carried out lessons in drill. The aim of its activity was training boys to the adult life, vocational education and also moral and religious upbringing. Orphanage of Duke O. Liubomyrskyj fund fulfilled its tasks good and did everything possible to support these children and to help theme. To master vocational education boys could thanks to opportunity to continue study by the best Krakow artificer, which was financed out of institutional fund. During the study boys continued to live by the institution. Social associations and private funds of Poland contributed much to organization of tutorial and upbringing work with orphan-children, completed guardianship organized by the charitable societies. The main their task was providing with necessary living conditions, primary education and vocational education of the orphans and arrangement of spare time but less attention was paid to the personality of children. For lack of assets associations and private funds could not give guardianship to the considerable amount of orphans. However orphans being under the guardianship became favorable conditions and diversiform help.